2013
DOI: 10.1007/s15010-013-0414-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and factors associated with influenza vaccination among subjects with asthma in Spain

Abstract: Seasonal influenza vaccination coverage among Spanish asthmatics is lower than desired and has not improved in recent years. Urgent strategies are necessary in order to increase vaccination coverage among asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…To address the question of such historically low vaccination rates among those with asthma, many studies employed cross‐sectional surveys to analyze the socio‐demographic variables that predict vaccine uptake. The strongest factors associated with higher vaccine coverage were older age, recent contact with healthcare providers, nonsmoking status, presence of comorbidities, more severe asthma, and (surprisingly) lower household income, although there are conflicting reports for the latter . Variables that were associated with lower vaccination uptake included younger age groups, belonging to certain ethnic groups, and lack of awareness about the vaccine .…”
Section: Current Influenza Vaccine Recommendations and Coverage For Pmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the question of such historically low vaccination rates among those with asthma, many studies employed cross‐sectional surveys to analyze the socio‐demographic variables that predict vaccine uptake. The strongest factors associated with higher vaccine coverage were older age, recent contact with healthcare providers, nonsmoking status, presence of comorbidities, more severe asthma, and (surprisingly) lower household income, although there are conflicting reports for the latter . Variables that were associated with lower vaccination uptake included younger age groups, belonging to certain ethnic groups, and lack of awareness about the vaccine .…”
Section: Current Influenza Vaccine Recommendations and Coverage For Pmentioning
confidence: 99%
“…However, vaccine uptake for clinical risk groups varied from 31% in Portugal to 82% in Northern Ireland, as did influenza vaccination coverage of adults with asthma, with 30%‐50% in Spain and 40% in the UK . Self‐reported uptake of seasonal influenza vaccine among adults with asthma in the United States varied from 54% in the community to 71% in secondary care .…”
Section: Current Influenza Vaccine Recommendations and Coverage For Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, an extensive review of the literature was carried out to identify the existing evidence on vaccination behavior. Previous studies have reported that people who are older [ 19 , 20 , 21 , 22 ], married [ 23 , 24 , 25 , 26 ], better educated [ 27 , 28 ], non-smokers [ 22 , 25 , 26 ], have chronic illnesses [ 16 ], no limitations on their activities [ 29 ], or who have medical insurance [ 29 ] are more likely to receive the vaccine than those without these characteristics. Conversely, research has shown that people who are allergic to medication [ 16 ] or smokers [ 30 ] are less likely to be vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…We presume that adolescents have considerably lower influenza vaccination rates than those getting free vaccination, and this has led to significant public health concerns. Although several studies have analyzed factors associated with influenza vaccination among adults with asthma [1,13,14], there have been few reports of vaccination rates and associated factors among adolescents with asthma [15,16]. We hypothesized that adolescents with asthma are more likely to get influenza vaccination than adolescents without asthma for the purpose of controlling their disease and preventing complications due to influenza infection.…”
Section: Introductionmentioning
confidence: 99%